Bartholdi Zeta Functions of Fractal Graphs - Sato, Iwao (The Electronic Journal of Combinatorics, 2009)
Recently, Guido, Isola and Lapidus defined the Ihara zeta function of a fractal graph, and gave a determinant expression of it. We define the Bartholdi zeta function of a fractal graph, and present its determinant expression.